INFLUENCIA DE LA POSICION DE LA COPA SOBRE LA FENOLOGIA y LAS RELACIONES HIDRICAS DEL ALCORNOQUE (QUERCUS SUBER L.) - Oliveira, G.; Werner, C.; Mertens, C.; Correia, O. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
A tree crown may be seen as a large and heterogeneous population of branches and leaves, unequally subjected to the environmental factors. It is thus questionable if studies on a few leaves or a branch will be a good approach to the whole canopy. This is particularly important in the field, where the applieation of ecophysiological measurements to mature (and generally large) trees presents obvious human and financial problems. The purpose of this study was to determine the effeet of different levels and directions within the' crown on the phenology and water relations of a typieal cork-oak in south Portugal. Our preliminary results show that the parts of the erown exposed to higher radiation value~ present a stronger growth and biomass production (direetion effect). Crown level was not clearly related to the results, suggesting that the "height effect" is not very important in trees with wide and diffuse crowns like the ones occurring in the montado systems.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Crown position; Phenology; Quercus suber; Stomatal eonductance 1)